Income Distribution and Current Account: A Sectoral Perspective - Till van Treeck; Jan Behringer (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2014)
We analyse the link between income distribution and the current account for the period 1972-2007. We find that rising (top-end) personal inequality leads to a decrease of the current account, ceteris paribus. This result is consistent with consumption externalities resulting from upward-looking comparisons. Moreover, an increase in the corporate financial balance or a decrease in the labour income share leads to an increase in the current account. This finding is consistent with the view that consumers do not fully pierce the corporate veil . Changes in personal and functional income distribution have contributed considerably to the widening of current account balances.
Keywords: D31; D33; F41; 330